The realist claim of fallibilism: A critique of the realism of Karl Popper - Fayos Febrer, Rafael (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
This article revises Karl Popper’s realism and examines how far he was a realist or simply he tried to be. Distinguishing between two areas of realism, a general one against the idealism, and the other more specific as part of the philosophy of the science, we analyze Popper’s realism coming to the conclusion that we are facing a fake, and at the same time, precarious realism. Popper was, in any case, a Kantian realist.